Penggunaan Panduan Teknik Self Instruction Sebagai Media untuk Meningkatkan Disiplin Diri Siswa SMA - Nawantara, Rosalia Dewi; Arofah, Laelatul; Setyaputri, Nora Yuniar (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2019)
Self-discipline is an important attribute that must be possessed by students. The reality at school is that there are students who have low self-discipline. Low self-discipline is characterized by behavior that violates the rules of school until arriving late to school, not using the complete school attributes, and some other violiations. This phenomenon should be of particular concern because low of self-discipline will affect the academic field of students. One technique in counseling services that can be used to improve self-discipline is self instruction technique. Self-instruction techniques focus on positive self-words that can control behavior. The self instruction technique in this research was applied through the media guide. The purpose of this study is to improve the self-discipline of high school students through self-instruction technical guidance. The research method used was an experimental one type pretest-posttest design. The population of this research is the XI grade students of SMAN 1 Srengat. The sampling technique used was purposive sampling. The data collection instrument used was a scale of self-discipline. Data results from these instruments were analyzed using paired sample tests with the help of SPSS for windows with a significance value of 0.004 <0.05. This means that there are differences in the level of student self-discipline before and after the self instruction technique guide is given. The difference shows that the self instruction technique guide is effective for improving the self-discipline of high school students.